Prostate Artery Embolization in the Setting of Prostate Cancer: Review and Opinion - Nainesh Parikh MD, MBA; Kosj Yamoah MD, PhD; Peter Johnstone MD; Javier Torres-Roca MD; Julio Pow-Sang MD; Daniel Fernandez MD, PhD; Anupam Rishi MD; G. Daniel Grass MD, PhD (Cancer Control)
Prostate Artery Embolization (PAE) is a novel minimally invasive angiographic technique that has been used effectively to treat men with lower urinary tract symptoms (LUTS) from benign prostatic hyperplasia (BPH). However, applications of PAE for men with prostate cancer have been minimally studied. This review serves as an update on the status of PAE in men with prostate cancer, as well as a discussion of emerging indications.